Epigenetic regulation of autophagy in neuroinflammation and synaptic plasticity - Bai, Isaac; Keyser, Cameron; Zhang, Ziyan; Rosolia, Breandan; Hwang, Jee-Yeon; Zukin, R. Suzanne; Yan, Jingqi (Frontiers in Immunology, 2024)
Autophagy is a conserved cellular mechanism that enables the degradation and recycling of cellular organelles and proteins via the lysosomal pathway. In neurodevelopment and maintenance of neuronal homeostasis, autophagy is required to regulate presynaptic functions, synapse remodeling, and synaptic plasticity. Deficiency of autophagy has been shown to underlie the synaptic and behavioral deficits of many neurological diseases such as autism, psychiatric diseases, and neurodegenerative disorders. Recent evidence reveals that dysregulated autophagy plays an important role in the initiation and progression of neuroinflammation, a common pathological feature in many neurological disorders leading to defective synaptic morphology and plasticity. In this review, we will discuss the regulation of autophagy and its effects on synapses and neuroinflammation, with emphasis on how autophagy is regulated by epigenetic mechanisms under healthy and diseased conditions. This review summarizes current knowledge on the role autophagy plays in the regulation of synaptic development/functions and the epigenetic regulation of autophagy. Aberrant epigenetic changes leading to autophagy dysregulation and the associated neuroinflammation in neurological diseases has also been discussed.